Pengaruh Variasi Ukuran Lebar Material Terhadap Karakteristik Termoelektrik Sistem C/CuO - Wulandari, Yolanda; Putra, Ananda; Nizar, Umar Kalmar; Riga, Riga (Departemen Kimia FMIPA UNP, 2024)
One of the factors that can affect the quality and characteristics of thermoelectric materials is the size of the material.. This study aims to determine how the effect of material size is varied in width and thickness. The material used is activated carbon obtained from previous research that has met the SNI No. 06-3720-1995 content test. The activated carbon is then composited with Copper (II) Oxide. Based on the tests that have been carried out, the best material obtained is the material with a width size variation of 1 cm. With a high electrical conductivity value of 0.0909 MΩ-.cm-, low thermal conductivity of 0.2418 J/s and has a high Seebeck coefficient of 0.0166 mV/K. Thermoelectricity offers sustainable energy to maintain energy needs, namely by converting wasted heat energy into electrical energy that can overcome the current global warming problem.